The Forest Heritage of Rosemary in the Taourirt Region - Eastern Morocco - Between Smuggling and Uprooting - Lakhdari, Mohammed; El-Bazoui, Jaouad; Aziach, Mohamed; Bouberria, Abdelouahed (Journal of agricultural, environmental and veterinary sciences, 2024)
The rural areas within the Taourirt Province, in Eastern Morocco, are rich in diverse natural resources (rosemary, alfa grass, pottery industry, charcoal, etc.), which have fostered a social knowledge adapted to the natural environment, creating a relationship of mutual influence. Rosemary is part of Morocco's strategy for the development of medicinal and aromatic plants. In the Taourirt Province, this plant covers an area of approximately 150,000 hectares, with an estimated production in the study area of more than 44,500 tons. However, the field study of the management of this vital resource – the forest heritage of rosemary – in the mountainous areas within the study region remains below expectations, limiting its sustainability and reducing the benefits derived from it. This situation highlights the need to strengthen governance in its exploitation and establish industrial units for local value enhancement, benefiting from its cancer-fighting and antioxidant properties, in addition to seeking ways to market the product domestically and internationally.
Keywords: natural resources; forest heritage; rosemary; territorial development; Taourirt Province; Eastern Morocco